Multidrug Resistance and Serotype Distribution of Salmonella Enterica Isolated from Homemade Recipe Fermented Ground Pork (Nham) in Northeastern Thailand - Vo, Thi-Hoang-Nga; Direksin, Kochakorn; Rattanadilok-Na-Phuket, Nawarat; Nutravong, Thitima; Kerdsin, Anusak (Trends in Sciences, 2022)
Salmonellosis is caused by a thousand serotypes of Salmonella enterica. The sour taste inherent to Nham leads people believe that this fermented ground pork dish is safe from pathogenic microorganisms. The aim of this study was to evaluate the prevalence, serotype, drug susceptibility, and antimicrobial resistance (AMR) genes of Salmonella spp. in homemade recipes of Nham. There were 52 samples from different Nham makers in 3 northeastern provinces of Thailand collected between August and November 2019. Further, 30 Salmonella isolates (57.7 %) and 14 different serovars were identified: S. Rissen (23.3 %) was the most prevalent, followed by S. Typhimurium (16.7 %), S. Give and S. Virchow (10 % each), and S. Agona and S. Kouka (6.7 % each). All isolates carried AMR genes but 7 (23.3 %) were antibiotic susceptible and 23 (76.7 %) borne a resistance phenotype. The Salmonella isolates were resistant to tetracycline (63 %), sulfamethoxazole/trimethoprim (36.7 %), streptomycin (33.3 %), nalidixic acid (30 %), cefotaxime (16.7 %), and enrofloxacin (3.3 %). Among the 23 AMR genes in our analysis, there were gyrB (100 %), tetA (93.3 %), aadA (93.3 %), sul1, sul2, sul3 (23.3 - 33.3 %), dfrA12 (16.7 %), qnrS, (6.7 %), and mcr6 (6.7 %). Two strains had the mcr6 gene but were susceptible to colistin. Our findings suggest that naturally occurring lactic acid bacteria in the Nham products are insufficient to inhibit Salmonella contamination of this pork-based food. HIGHLIGHTS Highly presence of Salmonella in fermented ground pork (Nham) All identified Salmonella isolates in the Nham have AMR genes A few Salmonella isolates carry AMR genes but are antibiotic susceptible Two Salmonella isolates contain the mcr6 gene but are susceptible to colistin